Perturb and observe maximum power point tracking approach for microgrid linked photovoltaic system - Kshirod Kumar Rout; Debani Prasad Mishra; Sivkumar Mishra; Suman Patra; Surender Reddy Salkuti (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
This paper develops a maximum power point tracking (MPPT) approach for a microgrid-linked solar photovoltaic (PV) system based on the concept of a perturb and observe (P&O) approach. It is an iterative algorithm that requires a starting point to trace the maximum power point tracking. This study proposes the P&O MPPT algorithm for a 3-ɸ grid-connected PV system. In this work, the PV system is modeled as a DC grid-connected PV system, and the MPPT algorithm is applied to that model. An MPPT application is used in this proposal to amplify the effectiveness of the PV array in face of any unsteady climatic circumstances. Hence, the highest energy could be secured out of the solar PV array and interfaced with the grid. The voltage source converter will empower defining of boundaries and greatest degrees of force from sunlight-based chargers in an efficient way. A few outcomes like the current, voltage and result power for each different mix have been noted.